Effect of Oral Administration of Astragalus ecbatanus Chloroform Extract on Acute and Chronic Pain in Balb/C Mice - Javad Ghasemian Yadegari; Ezatollah Fazeli Moghadam; Hazhir Golmohammadi; Setareh Dastyarhaghighi; Mehrdad Ghoulami; Hossein Mahmoudvand* (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Astragalus spp., have been used as a pain reliever in traditional medicine; therefore, in this study, we decided to evaluate the antinociceptive effects of Astragalus ecbatanus chloroform extract (AECE) in acute and chronic pain in male mice. Methods: The extract was obtained from aerial parts of A. ecbatanus with maceration method. The antinociceptive effect of AECE was determined by tail-flick, hot-plate, formalin, and rotarod tests followed by the oral intake of mice with AECE at the doses of 200, 400, and 800 mg/kg for 14 days in male Balb/C mice. Results: The results showed AECE at the concentrations of 400 and 800 mg/kg revealed a mean latency time of 6.4 and 7.2 s, respectively; representing a remarkable (p<0.05) antinociceptive activity compared with the control group. AECE, especially at the doses of 400 and 800 mg/kg, significantly increased the time until the occurrence of painful behaviors (licking or jumping) compared to the control group (p<0.001). The results showed AECE, especially in concentrations of 400 and 800 mg/kg, markedly (p<0.05) reduced the pain behaviors in the first phase (acute) and the second (chronic) phase of the formalin test compared to the control group. Conclusion: According to the reducing pain effect of this plant in both pain tests and in both stages of the formalin test, it can be concluded that Astragalus ecbatanus reduces both acute pain and chronic pain, and can relieve pain both peripherally and centrally.